New amide alkaloids from Piper longum fruits - Yang, Jun (Springer Berlin Heidelberg, 2013)
Three new amide alkaloids piperlongumamides A-C (1–3), together with 12 known ones (4–15), were isolated from the fruits of Piper longum. The structures of the new isolates were determined using spectroscopic data analyses. Cytotoxic activity of these amides against HL-60 (human leukemia), A-549 (human lung cancer), MCF-7 (human breast cancer), SMMC-7721 (human liver cancer) and SW480 (human rectal cancer) cell lines were evaluated. Piperchabamide B (11) exhibited weak inhibitory activity against HL-60 (IC(50) = 21.32 μM ), A-549 (IC(50) = 23.82 μM ) and MCF-7 (IC(50) = 16.58 μM ) cell lines. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-013-0073-0 and is accessible for authorized users.